Pengaruh Supervisi Akademik dan Manajerial Kepemimpinan Kepala Sekolah Terhadap Motivasi Kerja Guru di Gugus 25 SDN 2 Mata Ie Kabupaten Aceh Besar (Indo-MathEdu Intellectuals Journal, 2024)
The purpose of this study is to determine the influence of academic and managerial supervision of the principal's leadership on the work motivation of elementary school teachers in the SDN 25 Mata Ie Cluster, Aceh Besar Regency. This study used survey research method. The population in this study amounted to 73 primary school teachers. Data collection techniques using questionnaires. Hypothesis testing using simple linear regression analysis test, multiple linear regression analysis, multiple correlation analysis (R), determination analysis (R2), and regression coefficient test together (Test F). The results of the research are that there is a significant influence between academic supervision on teacher work motivation in the SDN 25 Mata Ie cluster, Aceh Besar Regency; There is a significant influence between the principal's managerial leadership on the work motivation of teachers in the 25 Mata Ie State Elementary School Cluster, Aceh Besar Regency; There is a significant influence between the principal's academic supervision and managerial leadership on teacher work motivation in the SDN 25 Cluster, Aceh Besar Regency; The contribution of academic supervision to teacher work motivation is 38.8%; The contribution of the principal's managerial influence to teacher work motivation is 51.3%; The magnitude of the contribution of the influence of the principal's academic supervision and managerial leadership on teacher work motivation is 57.8%.